Apoptosis induction of human bladder cancer cells by sanguinarine through reactive oxygen species-mediated up-regulation of early growth response gene-1. - Min Ho Han; Cheol Park; Cheng-Yun Jin; Gi-Young Kim; Young-Chae Chang; Sung-Kwon Moon; Wun-Jae Kim; Yung Hyun Choi (PLoS ONE, 2013)
Although the effects of sanguinarine, a benzophenanthridine alkaloid, on the inhibition of some kinds of cancer cell growth have been established, the underlying mechanisms are not completely understood. This study investigated possible mechanisms by which sanguinarine exerts its anticancer action in cultured human bladder cancer cell lines (T24, EJ, and 5637). Sanguinarine treatment resulted in concentration-response growth inhibition of the bladder cancer cells by inducing apoptosis. Sanguinarine-induced apoptosis was correlated with the up-regulation of Bax, the down-regulation of Bid and XIAP, the activation of caspases (-3, -8, and -9), and the generation of increased reactive oxygen species (ROS). The ROS scavenger N-acetyl cysteine (NAC) completely reversed the sanguinarine-triggered apoptotic events. In addition, sanguinarine effectively increased the activation of the c-Jun N-terminal kinase (JNK) and the expression of the early growth response gene-1 (Egr-1), which was recovered by pretreatment with NAC. Furthermore, knockdown of Egr-1 expression by small interfering RNA attenuated sanguinarine-induced apoptosis, but not the JNK inhibitor, indicating that the interception of ROS generation blocked the sanguinarine-induced apoptotic effects via deregulation of the expression of Egr-1 proteins. Taken together, the data provide evidence that sanguinarine is a potent anticancer agent, which inhibits the growth of bladder cancer cells and induces their apoptosis through the generation of free radicals.